Experimental investigation of polyethylene combustion in a solid fuel ramjet - Ferreira, J. Gobbo; Carvalho, J. A.; Silva, M. G. [UNESP] (American Institute of Aeronautics and Astronautics (AIAA), 1996)
The main objective of this paper is to report results of the regression rate of polyethylene in solid fuel ramjets when a hot stream of vitiated air passes through the combustion chamber. This rate is known to depend on chamber pressure and on air mass flow rate and temperature. An experimental expression for the regression rate was obtained for the conditions of the tests. Other features of this work are the introduction of an intermediate mixing chamber and a discussion of the effect of the increase of post mixing chamber length over combustion efficiency. Radiation transfer losses were also analyzed and discussed. This was accomplished by the use of a translucid polyethylene grain, which was first operated bare and later covered with an insulation aluminum sheet. Experimental results are analyzed, and their trend agrees with those showed in previous works conducted with systems of similar geometry and different fuels.